(3TQM NeQjI GHf GdaGQVs - (3CMeO Hf SdjeGf Hf ceGd HGTG GdQhej , TeS GdOjf,J (B940 (3g` s
(3ChdgG (B:s
(3TQHfG Ydi PcQ GdMHjH hbGd CHh YHjOI GdTQH HGdae YeOi hHGdNaV hGdae GSeGf ai TQHJ GdTQH s
(3BNQgG (B:s
(3hGdfUjH hGdSejY ef GdTF hcCfg CQGO HGdChd GdeYfi GdeYfi hHGdKGfi GdeYfi GdeHge aGage Je HMeO Gddg hYhfg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B21s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B133 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B238 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B141s
Keywords: (3GdeLGejYs